Bio-ecology and elemental composition of a giant : the ocean sunfish Mola mola - Baptista, Miguel (2019)
Around the world, numbers of large predatory fish have been declining at a considerable rate which may contribute to the severe destabilization of ecosystems. It is therefore vital to broaden the available knowledge on these animals in order to ensure their preservation and ecosystem functioning worldwide. The ocean sunfish Mola mola, is an example of a large predatory fish currently threatened, with an estimated global decline of 10% every decade. Within this context, the objective of the present dissertation was to increase the knowledge on this teleost on three understudied aspects, namely spatial use, growth and elemental composition. Mola mola were found to inhabit the southern waters of Portugal between April and November (study period), exhibiting two abundance peaks - spring and autumn. Additionally, it was observed that the overwhelming majority (98%) of specimens inhabiting the studied area were juveniles. The abundance of M. mola was positively correlated with both sea surface temperature and chlorophyll a concentration (proxy for productivity), indicating that a combination of these environmental factors dictates spatial use. With respect to growth, divergent growth patterns were observed for M. mola inhabiting different geographical areas. Concomitantly, the length-weight relationship constructed for North Atlantic M. mola was found to be statistically significantly different than that previously reported for North Pacific specimens and commonly accepted as representative of M. mola growth worldwide. Relatively to the trace element composition of juvenile M. mola, gender-related differences were found, mainly in the gonads and chiefly for essential elements (i.e. Cr, Mn, Co, Cu, Zn and Se). Overall, Zn and As were the elements observed in greater concentration in body tissues. Greater elemental loads were registered for the metabolically active tissues - liver and gills - whereas lowest loads were observed for white muscle, brain and gelatin (subcutaneous white gelatinous layer characteristic of ...